ANIMASI 3D PENDUKUNG SIMULASI FUNGSI FLIGHT CONTROLS DAN LANDING GEARS SUPRI SUKHOI SUPERJET 100 - Retnowati, Nurcahyani Dewi; Astuti, Yenni; Ermanto, Supri (Sekolah Tinggi Teknologi Adisutjipto, 2013)
Animations are one of multimedia technology which can accelerate the perspective about something, including the aircraft flight controls and landing gears function. Production process of animation on 3 Dimensional Aircraft model Supri Sukhoi Superjet 100 using NURBS Modelling method. Production process of animation on 3 Dimensional Aircraft model Supri Sukhoi Superjet 100 using Pre Production, Production and Post Production, that the result can be presented in the form of simulation video, Flash game, and Powerpoint game. The special effect that added into model, video and game make it more attractive. The Results are tested on number of respondents who are Experts in the Aircraft Engineering. The Data showed that Almost to 100 percent of the components and fuctions of the aircraft.